A Study of exposure behavior, utilization and satisfaction of users of the Department of Agricultural Extension Facebook - sensomboon, kulkanist; Bilmanoch, Sasiphan; Taphowtong, Wanitra (Siam Communication Review, 2024)
The purpose of this research is to study media exposure behavior utilization and satisfaction of the users of the Department of Agricultural Extension Facebook. The sample group was 400 Facebook followers of the Department of Agricultural Extension. This research was a quantitative research, and using online questionnaires as a tool for collecting data. The statistics used in data analysis are percentage, mean, and standard deviation. The results of the research found that most of users of the Department of Agricultural Extension Facebook were aged between 31 – 40 and majority working as government officer followed by farmers. Most of them followed the Department of Agricultural Extension Facebook 1 - 2 days a week and the spending time of using was less than 15 minutes during 16.01 - 20.00 pm. In this regard, the majority of the sample group's Facebook users behavior was to receive agricultural news in every aspect and to receive warning news about problems in the agricultural sector. Most of the user's utilization is to receive information about the advancement in agriculture to apply knowledge for their own career/work and then make decisions about participating in activities/projects. For the satisfaction of users, most of them satisfied with the content and the most reliable information